Zasilanie wycieków VI poziomu Kopalni Soli "Wieliczka" - Pisarek, Jakub (My University, 2018)
Water hazard in the Wieliczka mine is associated with sandy formations of the Chodenice layers existing on the northern side of the salt deposit. In history, all water penetrations of the mine originated at these formations. Quite less dangerous are spills from Quaternary and sub-salt deposits, technological brines (most spills on level VI) and leaks. Since 1993 liquidation works are performed in the central area of the mine targeted at achieving orogen stabilisation and securing the mine from new sudden inflows. Since 1999, gradual liquidation of leaks has been carried out, with simultaneous monitoring of their expenses, chemistry and conducting isotope research.

W Kopalni Soli „Wieliczka” zagrożenie wodne jest związane z występującymi po północnej stronie złoża solnego piaszczystymi utworami warstw chodenickich. W historii większość większych wdarć wody do kopalni pochodziło właśnie z wspomnianych utworów chodenickich. Dużo mniej groźnymi są wycieki z utworów czwartorzędowych, podsolnych, solanek technologicznych (większość wycieków na poziomie VI) oraz przecieki. Od 1993 roku prowadzono roboty likwidacyjne w centralnym rejonie kopalni dla uzyskania stabilizacji górotworu i zabezpieczenia kopalni przed nowymi dopływami awaryjnymi. Od 1999 roku realizowana jest stopniowa likwidacja wycieków przy jednoczesnym monitorowaniu ich wydatków, chemizmu oraz przeprowadzaniu badań izotopowych.
Recharge of leakages VI level Wieliczka Salt Mine
Załączniki do opisania
Keywords: Wieliczka Salt Mine; Kopalnia Soli Wieliczka; leakages; wycieki kopalniane; brine; solanka; level VI; poziom VI; chodenice; chodenice